A brief instrument to measure health-related quality-of-life in patients with bone metastasis: validation of the German version of Bone Metastases Quality-of-Life-10 (BOMET-QoL-10). (2nd September 2018) - Marschner, Norbert; Wilke, Jochen; Reschke, Daniel; Kaiser, Florian; Schmoor, Claudia; Grugel, Renate; Boller, Emil
Abstract: Aims: This prospective, epidemiologic study was designed to translate the original Spanish Bone Metastases Quality-of-Life-10 (BOMET-QoL-10) questionnaire and undertake a validation of the translated German version of BOMET-QoL-10 in Germany to assess health-related quality-of-life (HRQoL) in patients with bone metastases (BM). Methods: The translation process included forward and backward translations, and a linguistic validation. Patients aged ≥18 years with histological confirmation of cancer, diagnosed with BM, life expectancy ≥6 months, and fluency in German were eligible for this study (enrolled consecutively in 33 outpatient centers in Germany). Patients were given the German version of BOMET-QoL-10, together with the European Organization for Research and Treatment of Cancer (EORTC) Quality of Life Questionnaire QLQ-C30 and EORTC QLQ-BM22 questionnaires at inclusion, 6 weeks, 3 months, and 6 months after inclusion. A debriefing questionnaire was administered at inclusion to determine patient acceptability and understanding. Results: Data include 364 patients with BM (median age = 68 years; females = 71.7%). The BOMET-QoL-10 is brief and clear (median completion time = 5 minutes; >90% of patients completed the questionnaire without assistance). The BOMET-QoL-10 forms only one overall scale. All 10 items showed a substantial correlation with the first factor (factor loading, range = 0.58–0.86). BOMET-QoL-10 exhibits high internal consistency and reproducibility (Cronbach's alpha = 0.91; intra-class correlation coefficient = 0.76). BOMET-QoL-10 showed significant correlations (range = 0.69–0.79) both with EORTC QLQ-C30 and EORTC QLQ-BM22 within the functioning (physical, social, interference) and symptom (fatigue, pain) scales, displayed significant sensitivity to change in EORTC QLQ-BM22 scores, and proved the potential ability to detect change in HRQoL in patients with different disease status. Limitations: There was a high proportion of females in this study, which might represent a limitation. Conclusions: The German version of BOMET-QoL-10 is a valid, reliable, brief, and clear instrument able to measure HRQoL in patients with BM.